Troubleshooting analog circuits - Pease, Robert A.; Elsevier Science Publishers (Boston : Butterworth-Heinemann, 1993)
Based on the author's popular series in EDN Magazine, the book contains a wealth of information on debugging and troubleshooting analog circuits. In this book, you'll find advice on using simple equipment to troubleshoot (would you believe an ordinary AM radio?); step-by-step procedures for analog troubleshooting methods; and generous helpings of the author's unique insights, humor, and philosophy on analog circuits. *Provides proven methods for troubleshooting analog circuits *Accompanying disk contains over 60 pre-built Electronics Workbench circuits.
Includes bibliographical references and index.
Keywords: Linear integrated circuits -- Maintenance and repair; Electronic circuit design; Electronic books